Možnosti použití polymerních vláken s plazmovou úpravou v cementových kompozitech - Žižková, Lucie (Vysoké učení technické v Brně. Fakulta stavební, 2022)
Plazmová úprava představuje novou progresivní metodu, jak zvýšit užitné vlastnosti polymerních vláken. Práce je zaměřena na ověření efektu úpravy povrchu polymerních vláken do betonu nízkoteplotním plazmatem. Je popsána úprava polypropylenových vláken v nízkoteplotním plazmatu. Je hodnocen vliv této úpravy na objemové změny cementových kompozitů. A dále je provedeno experimentální ověření vlivu přídavku komerčně dostupných vláken a vláken upravených plazmatem na objemové změny cementových kompozitů.

The usage of polymer fibres can be increased by the new progressive method of the plasma treatment. This thesis is focused on verification of the influence of the low-temperature treatment on polymer fibres´ surface used in concrete. The treatment of polypropylene fibres in low-temperature plasma is described in the theoretical part. The impact of the treatment on the volume differences of cement composites is also evaluated. The influence of the addition of commercially available fibres and plasma treated fibres on the volume differences of cement composites is also experimentally verified.
Fibre reinforcement with plasma in cement composites
Keywords: Cementový kompozit; polymerní vlákna; polypropylenová vlákna; plazma; nízkoteplotní plazma; rozptýlená výztuž; beton; objemové změny; smrštění; smršťovací trhliny; Cement composite; polymer fibres; polypropylene fibres; plasma; low-temperature plasma; sparse reinforcement; concrete; volume differences; contraction; shrinkage cracks